Supplier Involvement, Digital Supply Chain, and Green Supply Chain on Competitiveness: The Mediating Effect of Supply Chain Resilience - Iwan Nauli Daulay; Nurul Aini; Farah Andrian; Apriska Nur Oktavia (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Increasing business uncertainty and supply chain disruptions require MSMEs to strengthen their resilience to remain competitive. This study aims to analyze the influence of supplier involvement, digital supply chain, and green supply chain management on competitiveness through supply chain resilience as a mediating variable in food and beverage MSMEs in Pekanbaru City. The research adopts a quantitative approach with a cross-sectional design, involving 60 respondents selected through purposive sampling. Data were collected using questionnaires and analyzed using the SEM-PLS approach through SmartPLS software. The results show that all constructs meet validity and reliability criteria, and the structural model has strong explanatory power. Supplier involvement, digital supply chain, and green supply chain management have positive and significant effects on both supply chain resilience and competitiveness, while supply chain resilience also positively influences competitiveness. Additionally, supply chain resilience partially mediates these relationships. Strengthening supplier collaboration, digitalization, and sustainable practices enhances resilience, which in turn improves MSME competitiveness. This study contributes theoretically by integrating multiple determinants of competitiveness within a comprehensive model and offers practical implications for MSMEs to develop adaptive, resilient, and sustainable supply chain strategies in a dynamic business environment.